Pre-strain effects on CYTOP fibre Bragg grating temperature sensors - Pospori, A.; Ioannou, A.; Kalli, K. (My University, 2022)
Cyclic transparent optical polymer (CYTOP) based fibre Bragg grating (FBG) sensors are of high interest recently due to their lower optical loss compared with the sensors fabricated in other polymeric materials, such as poly(methyl methacrylate). Numerous scientific reports have shown that polymer based FBGs are usually preferred over their silica counterparts due to their enhanced sensitivity to stress and pressure, and their affinity to humidity. Temperature monitoring with polymer FBGs is also extensively demonstrated, but with inconsistent results and non-linear responses, since most of the polymer optical fibres have a negative thermo-optic coefficient and positive thermal expansion coefficient that work to cancel out each other to some extent, resulting in mixed temperature sensitivities. In this work, an optical fibre with a CYTOP core and a Xylex cladding is used to investigate fibre pre-strain effects on the temperature sensitivity of FBG sensors. The sensors were placed in an environmental chamber with controlled temperature and relative humidity, and their response to temperature was evaluated under various fibre pre-strain values. Without any applied fibre strain, the thermal expansion coefficient slightly prevails over the thermo-optic effect, as a result the Bragg wavelength shifts in longer wavelengths. Under sufficient fibre strain, the thermal expansion coefficient is eliminated, and the temperature sensitivity is greatly enhanced, shifting the Bragg wavelength to shorter wavelengths. This paper demonstrates the possibility to have an array of Bragg grating sensors, some being temperature insensitive and some highly temperature sensitive along the same fibre.
Keywords: fibre Bragg grating sensors; optical polymer